Communicating to children about the COVID-19 pandemic - Grace J. Soma (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2020)
The end of 2019 ushered in a new decade and the spread of a novel coronavirus causing respiratory symptoms and disease confirmed as an outbreak by the World Health Organization (WHO) in January 2020. The International Committee on Taxonomy of Viruses (ICTV) declared on 11 February 2020 that "severe acute respiratory syndrome coronavirus 2" (SARS-CoV-2) was the name of this new virus due to its genetic similarity to the coronavirus responsible for the SARS outbreak of 2003. The disease caused by this virus was designated the name coronavirus disease of 2019 (COVID-19) by the WHO for purposes of risk communication to the general public